Standard setting methods in objective structured clinical examination (OSCE): A comparative study of five methods - Mohamed Ansari, Reshma; Ab Manan, Norhafizah; Mahat, Nur Ain; Omar, Norfaizatul Shalida; Abdul Latiff, Atikah; Idris, Sara; Othman, Azli Shahril (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Objective Structured Clinical Examination (OSCE) is a crucial component in medical school examinations to assess students’ competency, particularly in clinical skills incorporating cognitive and affective domains. OSCE results are subjected to standard-setting methods, which yield different findings. Hence, in this study, five different standard-setting methods, namely norm reference, Angoff method, borderline group method (BGM), borderline regression method (BRM), and modified Cohen’s method, were compared to determine the cut-off scores and failure rates determined by each method. Material & Methods: Data of 170 second-year medical students who attended OSCE with eight stations for their First Professional Examination at the end of year 2 MBBS was taken for the study following ethical approval. Total scores for each station were standardized to 20 marks, and cut-off scores were determined using each of the five standard-setting methods. Results: As a comparison of 5 methods, the Norm reference method yielded the highest number of stations with high cut-off scores, followed by BRM. This is reflected in the number of failures, too. On the contrary, using the Angoff method yielded the lowest cut-off scores in maximum stations, resulting in the least number of failed students. The Cochrane’s Q test of the results yielded a p < 0.001, which signifies that the proportion of students who failed a particular OSCE station was significantly different when different methods were used to determine the cut score. Conclusion: The study, which compared 5 common standard-setting methods employed in medical education assessments, found that norm-referenced and BRM had high cut-off scores and failures, with the opposite determined by the Modified Angoff method. The study concluded that the cut-off score and failure rate differed with different standard-setting methods, and the choice of the method is contextual depending on the available resources.